Acute and critical care medicine at a glance - Leach, Richard M.; Leach, Richard M. (The at a glance series, 2009)
Part of the 'At a Glance' series, this book provides a simple and straightforward introduction to the care of the critically ill. This new edition benefits from the addition of a section on acute medicine - a discipline that has developed rapidly in recent years.